The information structural effects of German P- and D-pronouns in discourse - Bittner, Dagmar; Dery, Jeruen E. (ZAS Papers in Linguistics, 2015)
The present investigation steps back to the claims of the 1990s by assuming that there is a functional opposition in the use of P- and D-PRO which affects the status of the pronoun's referent in the mental model of the discourse. We interpret the earlier findings as an indication of an information structural difference which is specifically relevant on the discourse level. The question we address here is twofold. Firstly, we ask whether the assumed opposition in the information status of P- and D-PRO referents has consequences on referent continuation in the ongoing discourse. So far, the effects of P- vs. D-PRO use were determined concerning the status of the pronoun referent in the actual sequence of discourse, i.e. they were determined by a judgement on the salience or the topic/focus status of the pronominal DP. As far as we can see, this determination has not been operationalized further. Since there are contexts in which both P- and D-PRO would fit in with only a feeling of a difference but without clear-cut exclusiveness, the opposition is empirically not well validated. If we could show that there are effects of type of pronoun on the ongoing discourse this would, in our view, provide the lacking empirical validation. Secondly, we ask whether there are effects of the narrator's point of view on P- and D-PRO use. The idea behind this question is that the way of information unfolding in discourse depends on the speaker. S/he decides which pieces of information come next, what is foreground and what is background information. If type of pronoun choice is related to the processes of discourse organization by the speaker – via fore- and backgrounding of information – and if internal or external location of the narrator's point of view influences the organization strategies of the speaker/narrator this might have an ffect on the use of P- and D-PRO.